An unusual location of micronodular thymoma with lymphoid stroma: A posterior mediastinal mass invading into pleura - Utku Ekin; Ahmad M. Alkhatatneh; Lan Wang; Mourad Ismail (Human Pathology Reports, 2023)
Micronodular thymoma with lymphoid stroma (MNTL) is a rare type of thymoma that is often found alongside Type A thymoma. Here, we present a case of MNTL diagnosed in an 82 year-old-female who had a thymus excision seven years prior. The posterior mediastinal mass was discovered incidentally in this patient after a mechanical fall and diagnostic imaging. The patient underwent a needle biopsy of this mass, the pathology of which initially demonstrated type A thymoma. Several months later, the patient underwent a video-assisted thoracoscopic surgery (VATS) procedure with resection of the mass. Pathology this time showed mixed areas of MNTL, type B3, and focal B2 types of thymoma. The location and the histological morphology of this tumor were unique. Treatment approaches to such cases should be multidisciplinary and individualized.